Pengembangan Media Flipbook Dalam Pembelajaran IPS Pada Siswa Kelas III SD - Widiya Widiya (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research is motivated by developments in the times that are increasingly leading to technology. Therefore, research that uses technology as a learning medium, namely flipbooks as a piece of software that can facilitate the learning process for third-grade elementary school students on the material "I am part of society" where in the previous learning process they still used manual media such as print media, namely book.The aim of the researcher in doing this is to find out how the flipbook media has developed in grade III elementary school social sciences learning, and whether this media can make it easier for students to understand the lessons being taught and is suitable for use.The method used in this research is to use a Literature Review which is by: 1). Collect data or information, 2). Evaluating data, theory, information, or research results, 3). Analyze results in publications such as books, research articles, or those related to research questions. The results of this research are utilizing technology which makes flipbook-based learning media a very good and accurate medium and can be used as a guide for overcoming educational problems in student learning.